A clinical study of acute pancreatitis - R., Narender N.; Pappu, Kameshwari Prasad (International Surgery Journal, 2016)
Background: Acute pancreatitis is an acute inflammatory process of the pancreas with varying involvement of other regional tissues or remote organ systems. About 80% of the attacks are mild, 20% are severe and they are commonly accompanied by necrosis of the pancreas and or organ failure. The objective of the study was to determine the correlation between Ranson’s score, CT severity index and pancreatic enzymes in acute pancreatitis. Methods: In the present study 150 patients were included who had clinical features of acute pancreatitis and CECT abdomen suggestive of acute pancreatitis. Patients with chronic pancreatitis were excluded from the study. Patients were admitted to the hospital and CECT abdomen was performed 48 hours after the onset of symptoms. Liver function tests, complete blood picture, serum calcium and pancreatic enzymes were assessed at the time of admission, after 48 hrs and weekly thereafter till discharge. Patients were followed up with regular spontaneous visits, telephonic intimation and through postcard. Results: Majority of the patients were in the age group of 20-40 (72%). It was more common in males (m:f)=(9:1). In general, ethanol abuse was more common cause while in females gall stone was the major cause. There was a good correlation between Ranson’s score and CT severity index score. The magnitude of enzyme elevation had no correlation with the severity of the disease. On follow up common complications were Pseudo cyst of the pancreas, Splenic vein thrombosis, Left sided pleural effusion. Conclusions: This study concludes that there is a good correlation between CT severity index and Ranson’s score with respect to severity of the acute pancreatitis. Serum amylase and lipase levels have little role in terms of severity of acute pancreatitis.